Effect of ß-alanine supplementation during high-intensity interval training on repeated sprint ability performance and neuromuscular fatigue - Milioni, F.; de Poli, R. A. B.; Saunders, B.; Gualano, B.; da Rocha, A. L.; Sanchez Ramos da Silva, A.; de Tarso Guerrero Muller, P.; Zagatto, A. M. (Journal of Applied Physiology, 2019)
The study investigated the influence of beta-alanine supplementation during a high-intensity interval training (HIIT) program on repeated sprint ability (RSA) performance. This study was randomized, double-blinded, and placebo controlled. Eighteen men performed an incremental running test until exhaustion (TINC) at baseline and followed by 4-wk HIIT (10 × 1-min runs 90% maximal TINC velocity [1-min recovery]). Then, participants were randomized into two groups and performed a 6-wk HIIT associated with supplementation of 6.4 g/day of beta-alanine (Gbeta) or dextrose (placebo group; GP). Pre- and post-6-wk HIIT + supplementation, participants performed the following tests: 1) TINC; 2) supramaximal running test; and 3) 2 × 6 × 35-m sprints (RSA). Before and immediately after RSA, neuromuscular function was assessed by vertical jumps, maximal isometric voluntary contractions of knee extension, and neuromuscular electrical stimulations. Muscle biopsies were performed to determine muscle carnosine content, muscle buffering capacity in vitro (betamin vitro), and content of phosphofructokinase (PFK), monocarboxylate transporter 4 (MCT4), and hypoxia-inducible factor-1alpha (HIF-1alpha). Both groups showed a significant time effect for maximal oxygen uptake (Gbeta: 6.2 ± 3.6% and GP: 6.5 ± 4.2%; P > 0.01); only Gbeta showed a time effect for total (-3.0 ± 2.0%; P = 0.001) and best (-3.3 ± 3.0%; P = 0.03) RSA times. A group-by-time interaction was shown after HIIT + Supplementation for muscle carnosine (Gbeta: 34.4 ± 2.3 mmol·kg-1·dm-1 and GP: 20.7 ± 3.0 mmol·kg-1·dm-1; P = 0.003) and neuromuscular voluntary activation after RSA (Gbeta: 87.2 ± 3.3% and GP: 78.9 ± 12.4%; P = 0.02). No time effect or group-by-time interaction was shown for supramaximal running test performance, betam, and content of PFK, MCT4, and HIF-1alpha. In summary, beta-alanine supplementation during HIIT increased muscle carnosine and attenuated neuromuscular fatigue, which may contribute to an enhancement of RSA performance. NEW & NOTEWORTHY beta-Alanine supplementation during a high-intensity interval training program increased repeated sprint performance. The improvement of muscle carnosine content induced by beta-alanine supplementation may have contributed to an attenuation of central fatigue during repeated sprint. Overall, beta-alanine supplementation may be a useful dietary intervention to prevent fatigue.